Gombrowicz a polski film fabularny - Nowakowski, Jacek (Przestrzenie Teorii, 2013)
This article presents the influence that Witold Gombrowicz’s work has had on Polish cinema. It covers several generations of directors, for example, Andrzej Munk (born in the 1920s), Roman Polański and Jerzy Skolimowski (born in the 1930) as well as Agnieszka Holland, Piotr Szulkin and Marek Koterski (born in the 1940s and 1950s), and discusses the topic of film adaptations of his books (Jerzy Skolimowski’s Ferdydurke and Jan Jakub Kolski’s Pornografia [Pornography]). The article shows that Polish cinema uses Gombrowicz’s works most of all by taking up the issue of life’s authenticity and inauthenticity as well as to demythologize Polish tradition and history. As for esthetics, it employs Gombrowicz’s favorite style, i.e. the grotesque.